Layered positive electrode material of high-capacity sodium-ion battery and preparation method of layered positive electrode material

By using single crystal O3 chemical formula Na1+aM1(1-b)M2bO2 in the sodium ion battery layered positive electrode material, and using high-pressure homogeneity reaction and high-temperature sintering technology, a positive electrode material with a single crystal morphology was prepared, which solved the problem of poor electrochemical performance and cycle performance caused by the increase of stress during the circulation of existing materials, and achieved high capacity and excellent cycle performance.

CN120072923APending Publication Date: 2025-05-30ZHEJIANG NATRIUM ENERGY CO LTD

Patent Information

Application Number
CN202510065739.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

The existing sodium ion battery layered positive electrode materials have increased stress due to the random crystal orientation changes of primary particles during the circulation, resulting in poor electrochemical and cyclic performance of the material.

Method used

Single crystal O3 type Na1+aM1(1-b)M2bO2 is used as layered positive electrode material, and a positive electrode material with a single crystal morphology is prepared through high-pressure homogeneity reaction and high-temperature sintering process. The transition metal elements M1 of this material are a mixture of Ni, Fe, Mn, Co, and Zr, and the doping elements M2 are a mixture of Ca, Cu, Sr, Al, Ti, Zn, Zr, and Mg.

Benefits of technology

The positive electrode material with single crystal morphology effectively limits the surface reactivity and particle cracking, improves the material's cycle life and discharge specific capacity, while maintaining excellent cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072923A_ABST
    Figure CN120072923A_ABST
Patent Text Reader

Abstract

The invention discloses a high-capacity sodium ion battery layered positive electrode material and a preparation method thereof, and relates to the technical field of sodium ion batteries, the high-capacity sodium ion battery layered positive electrode material is characterized in that the layered positive electrode material is a single crystal O3 type, the chemical formula of the layered positive electrode material is Na1 + aM1 (1-b) M2bO2, a is more than or equal to 0.00 and less than or equal to 0.05, and b is more than or equal to 0.1 and less than or equal to 0.3; m1 is a transition metal element, M2 is a doping element, and M1 is selected from one or more than two of Ni, Fe, Mn, Co, Zr and Cu; m2 is selected from one or more than two of Ca, Cu, Sr, Al, Ti, Zn, Zr, Mg and Co; the high-capacity sodium-ion battery layered positive electrode material is applied to a sodium-ion battery, and has excellent discharge specific capacity and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium-ion batteries, and in particular to a high-capacity sodium-ion battery layered cathode material and a preparation method thereof. Background Art

[0002] In today's world, with the continuous development of technology and economy, people's demands for life are constantly increasing, and at the same time, the demand for energy consumption is gradually increasing. The rapid growth of energy consumption demand is mainly due to the rapid rise in people's demand for electric energy, but the fuel structure in the power generation system still mainly relies on traditional fossil fuels. However, due to the non-renewability of fossil fuels in the short term and their adverse effects on the global climate and environment during the development and use process. Therefore, for the sustainable development of environmental resources and the steady progress of human society, it is necessary to optimize the existing energy system and strengthen the support and guidance for the development of renewable energy.

[0003] The key to improving the utilization of renewable energy lies in the construction and development of energy storage systems. Various countries are developing various new renewable energy sources, such as wind energy, solar energy, tidal energy, etc. However, the above-mentioned energy sources are easily affected by natural factors, causing impacts on the power grid and cannot be directly applied. For this, electrochemical energy storage technology is generally adopted at present. Electrochemical energy storage technology mainly refers to secondary battery technology, which has the characteristics of easy maintenance, flexibility, high energy storage and conversion efficiency, including zinc-air batteries, lithium-ion batteries, sodium-ion batteries, etc. Among them, lithium-ion batteries have attracted much attention due to their long cycle life, high energy density and high working voltage. However, lithium-ion batteries are limited by the lithium resource reserves and it is difficult to support the development of electric vehicles and large-scale energy storage at the same time. Therefore, it is necessary to develop new energy storage battery technologies to support their sustainable development. In recent years, sodium-ion batteries have received extensive attention due to having the same working principle as lithium-ion batteries and similar battery components, and due to advantages such as rich sodium resources, low cost and good comprehensive performance.

[0004] The cathode materials of sodium-ion batteries are mainly divided into oxide-based, polyanion-based, and Prussian blue and its analogs. Among them, layered oxides have a periodic layered structure, simple preparation methods, relatively high specific capacity and voltage, and are the mainstream materials currently under research. The currently commercially available layered oxides mainly include copper-containing nickel-manganese-iron-copper-based oxides and nickel-iron-manganese-based oxides. In order to further obtain higher capacity and better cycle performance, the materials are often doped and modified and surface-coated. For example, in patent CN116332244A, Mg is doped in the precursor of nickel-iron-manganese cathode material (NFM), 2+ and cobalt phosphate is coated outside the precursor. Among them, Mg 2+The addition can provide a part of free electrons, thereby generating holes or electrons and improving the electrical conductivity of the material. Coating cobalt phosphate helps reduce the residual alkali content on the material surface and improve the material stability. Patent CN 117239081A introduces Li, B, and F as composite doping elements in the NFM material, and simultaneously performs Al-Zn multi-element synergistic coating on the surface of the cathode material, enabling the material to exhibit good cycle stability and rate performance. A sodium-ion cathode material disclosed in CN118198316A includes an O3-phase layered material main body and a self-assembled heterojunction solid electrolyte coated on the surface of the O3-phase layered material main body. The final product is obtained by one-time sintering of oxides. By sintering a mixed material containing Na element, A element, M element, Q element, and T element, an O3-phase layered material main body is formed, and a heterojunction solid electrolyte is self-assembled on the surface of the O3-phase layered material main body.

[0005] However, it should be noted that the above materials are all secondary particles composed of primary particles. After assembling into a battery, the electrolyte can penetrate the secondary particles through the gaps between the crystal particles. In addition, during the cycling process, the random crystal orientation of the primary particles will generate significant stress with the change of their volume, thereby promoting horizontal cracking of the primary and secondary particles and further affecting the electrochemical performance and cycling performance of the material.

[0006] In response to this, the most promising method to alleviate the above problems is to prepare single-crystal materials. The single-crystal morphology can effectively limit the surface reactivity and particle cracking, greatly improving the cycle life of the material. However, since the sodium-ion transport path of the single-crystal morphology material becomes longer, the capacity of the material decreases. And the preparation method (molten salt synthesis) of single-crystal materials is difficult, which limits the use of single-crystal materials in preparation. Therefore, there is an urgent need to develop a high-capacity single-crystal sodium-ion battery layered cathode material and its preparation method. Summary of the Invention

[0007] The first aspect object of the present invention is to provide a high-capacity sodium-ion battery layered cathode material.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A high-capacity sodium-ion battery layered cathode material, characterized in that: the layered cathode material is a single-crystal O3 type, and its chemical formula is: Na 1+a M 1 (1-b) M 2 b O 2 where 0.00 ≤ a ≤ 0.05, 0.1 ≤ b ≤ 0.3; M 1 is a transition metal element, M 2 is a doping element, and the M 1Selected from one of Ni, Fe, Mn, Co, Zr, Cu or two or more thereof; said M 2 Selected from one of Ca, Cu, Sr, Al, Ti, Zn, Zr, Mg, Co or two or more thereof.

[0010] A layered cathode material for a high-capacity sodium-ion battery according to the present invention has a single-crystal morphology under a scanning electron microscope.

[0011] The further settings are as follows:

[0012] In the chemical formula of the layered cathode material for the sodium-ion battery, 0.01 ≤ a ≤ 0.03.

[0013] Said transition metal element M 1 Is a mixture of Ni, Fe, Mn, Zr, 0.8 ≤ 1 - b ≤ 0.9, wherein the element molar ratio of Ni, Fe, Mn, Zr is 0.30 - 0.32: 0.30 - 0.32: 0.30 - 0.32: 0.01 - 0.10.

[0014] Said doping element M 2 Is a mixture of Ca, Ti, Mg, 0.1 ≤ b ≤ 0.2. Among them, the element molar ratio of Ca, Ti and Mg is 4 - 6: 2 - 4: 4 - 6.

[0015] The shape of the single-crystal morphology particles of the layered cathode material is one of spherical, quasi-spherical, polyhedral, flaky or a mixture of two or more thereof.

[0016] The particle size D of the layered cathode material v Is 2 - 15 μm.

[0017] The ratio of I(003):I(104) in the XRD of the layered cathode material is 0.6 - 0.8.

[0018] The BET value of the layered cathode material is 0.4 - 1.0 m 2 / g.

[0019] Particularly preferably, in the chemical formula 1 of the layered cathode material, a = 0.03; the transition metal element M 1 Is a mixture of Ni, Fe, Mn, Zr, wherein the element molar ratio of Ni, Fe, Mn and Zr is 0.32: 0.32: 0.32: 0.04; the doping element M 2 Is a mixture of Ca, Ti, Mg, wherein the element molar ratio of Ca, Ti and Mg is 5: 3: 5, b = 0.13.

[0020] Particularly preferably, the shape of the single-crystal morphology particles of the layered cathode material is flaky; the particle size D v50 is 4 - 10 μm; the ratio of I(003):I(104) in the XRD of the layered cathode material is 0.63 - 0.66; the BET value is 0.4 - 0.7 m 2 / g.

[0021] The second object of the present invention is to provide a preparation method of a high - capacity sodium - ion battery layered cathode material, comprising the following steps:

[0022] (a) Combine sulfates containing element M 1 to form a transition metal salt solution with a certain concentration, add a precipitating agent sodium hydroxide solution and a complexing agent ammonia water into a high - pressure homogenizer, carry out a high - pressure homogenization reaction at a certain temperature, pH and pressure, and after the reaction is completed, transfer to aging, filtration, washing, and drying to obtain a cathode material precursor;

[0023] (b) Put the cathode material precursor, sodium source, and doping element M 2 into a blender in a certain proportion, stir and mix at a certain rotation speed to obtain a blend, sinter the blend in a certain atmosphere and at a certain temperature, and pulverize to obtain a single - crystal O3 - type high - capacity sodium - ion battery layered cathode material.

[0024] Further settings are as follows:

[0025] In step (a):

[0026] Preferably, combine sulfates containing element M 1 to form a 1 - 3 mol / L transition metal salt solution, add a 3 - 5 mol / L precipitating agent sodium hydroxide solution and 4 - 6 g / L complexing agent ammonia water into a high - pressure homogenizer, carry out a high - pressure homogenization reaction at a temperature of 40 - 60 °C, pH of 10 - 12 and pressure of 20 - 40 MPa, age for 10 - 14 h after the reaction is completed, filter, wash, and dry to obtain a cathode material precursor.

[0027] The transition metal element M 1 is a mixture of Ni, Fe, Mn, and Zr.

[0028] Particularly preferably, combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate according to the element molar ratio Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04 to form a 2 mol / L transition metal salt solution, add a 4 mol / L precipitating agent sodium hydroxide solution and 5 g / L complexing agent ammonia water into a high - pressure homogenizer, carry out a high - pressure homogenization reaction at a temperature of 50 °C, pH of 11 and pressure of 30 MPa, age for 12 h after the reaction is completed, filter, wash, and dry to obtain a cathode material precursor Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04(OH) 2 。

[0029] In step (b):

[0030] Preferably, the precursor of the cathode material, the sodium source, and the doping element M 2 are put into a blender in a certain proportion and stirred and mixed at a rotation speed of 300 - 500 rpm to obtain a blend. The blend is sintered at 400 - 600 °C for 4 - 6 h in a specific atmosphere and then sintered at 900 - 1100 °C for 10 - 20 h, and then pulverized to obtain the layered cathode material for high-capacity sodium-ion batteries.

[0031] The sodium source is one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate or a mixture of two or more of them.

[0032] The doping element M 2 is a mixture of Ca, Ti, and Mg.

[0033] The Ca-containing compound is one of calcium carbonate, calcium oxide, calcium peroxide, calcium hydroxide, calcium sulfate or a mixture of two or more of them.

[0034] The Ti-containing compound is one of titanium oxide, titanium hydroxide, titanium dichloride, titanium trichloride, titanium tetrachloride, metatitanic acid or a mixture of two or more of them.

[0035] The Mg-containing compound is one of magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium nitrate, magnesium acetate or a mixture of two or more of them.

[0036] Preferably, the sodium source is sodium carbonate, the Ca-containing compound is calcium carbonate, the Ti-containing compound is titanium hydroxide, the Zr-containing compound is zirconium hydroxide, and the Mg-containing compound is magnesium oxide.

[0037] Particularly preferably, the above-mentioned precursor of the cathode material, sodium carbonate, and the doping element M 2 (a mixture of calcium carbonate, titanium hydroxide, and magnesium oxide, with an element molar ratio of Ca:Ti:Mg = 5:3:5) are put into a blender according to the element molar ratio of Na:M 1 :M 2 = 1.03:0.87:0.13 and stirred and mixed at 400 rpm to obtain a blend. The blend is sintered at 500 °C for 5 h in an air atmosphere and then sintered at 1000 °C for 15 h, and then pulverized to obtain the layered cathode material for high-capacity sodium-ion batteries.

[0038] The third aspect of the present invention aims to provide an application of the above-mentioned layered cathode material for high-capacity sodium-ion batteries in the preparation of sodium-ion batteries. It is particularly suitable for two-wheeler batteries or power batteries.

[0039] Compared with the prior art, the present invention has the following advantages:

[0040] (1) The positive electrode material prepared by the present invention is flaky single crystal particles. There are no grain boundaries inside the single crystal material, which can effectively cope with grain boundary fragmentation and the penetration of the electrolyte, thereby improving the cycling performance of the material.

[0041] (2) By the coprecipitation method, the elements of the precursor are uniformly mixed in the present invention. By controlling the pH, concentration, reaction temperature and time, the morphology and physicochemical properties of the precursor are adjusted to make it more suitable for the preparation of single crystal positive electrode materials.

[0042] (3) When synthesizing the positive electrode material, Ti is doped into the transition metal in the present invention. Due to the relatively large bond energy of Ti-O, the TM-O bond shrinks, and O-O also shortens due to Ti 4+ doping. The TMO 2 layer shrinks. At the same time, Ti 4+ doping reduces the proportion of Mn 3+ / 4+ , reduces the Jahn-Teller effect, which is beneficial to improving the structural stability of the positive electrode material and improving the cycling performance. Zr and Ca can expand the unit cell parameters of the positive electrode material due to their relatively large ionic radii, which is beneficial to the diffusion of sodium ions and has excellent discharge specific capacity. The addition of Mg element can effectively inhibit the Jahn-Teller effect of Mn, enabling the material to have good cycling performance under high voltage.

[0043] (4) At a relatively high degree of cation mixing (I003 / I104), the material still has a high discharge specific capacity and excellent cycling performance.

[0044] (5) The preparation method provided by the present invention is a high-temperature calcination method. The preparation method is simple, suitable for industrial production, and environmentally friendly.

[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments recorded in the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is the SEM diagram of the precursors prepared in Comparative Example 1 and Example 10 of the present invention.

[0047] Figure 2 It is the XRD diagram of the layered positive electrode materials prepared in Comparative Example 1 and Example 10 of the present invention.

[0048] Figure 3SEM images of the layered cathode materials prepared in Comparative Example 1 and Example 10.

[0049] Figure 4 Charge-discharge curve of the layered cathode material prepared in Comparative Example 1.

[0050] Figure 5 Charge-discharge curve of the layered cathode material prepared in Example 10.

[0051] Figure 6 Cycling curve (1C) of the layered cathode materials prepared in Comparative Example 1 and Example 10. Specific implementation methods

[0053] The present invention will be explained in more detail below by specific embodiments. However, it should be understood that the specific functional details disclosed in this specification should not be construed as restrictive, but only as the basis of the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in any appropriate detailed embodiment in fact.

[0054] Example 1

[0055] (a) A transition metal salt solution with a concentration of 3 mol / L was prepared by combining nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate in an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Then, it was added to a high-pressure homogenizer together with a 4 mol / L precipitant sodium hydroxide solution and a 5 g / L complexing agent ammonia water. High-pressure homogenization reaction was carried out at a temperature of 50 °C, a pH of 12, and a pressure of 30 MPa. After the reaction, it was aged for 10 h, filtered, washed, and dried to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 .

[0056] (b) The precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, titanium hydroxide, and magnesium oxide with an elemental molar ratio of Ca:Ti:Mg = 4:3:6) were put into a blender according to a molar ratio of Na:A:B = 1.05:0.87:0.13 and stirred and mixed at a rotation speed of 300 rpm to obtain a blend. The blend was sintered in an air atmosphere at 400 °C for 5 h and then at 1000 °C for 15 h, and then pulverized to obtain a single-crystalline morphology sodium-ion battery layered cathode material Na 1.05 A 0.87 B 0.13 O 2 .

[0057] Example 2

[0058] (a) A transition metal salt solution with a concentration of 1 mol / L is prepared by combining nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate in an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. This solution, along with a 3 mol / L precipitating agent sodium hydroxide solution and a 5 g / L complexing agent ammonia water, is added to a high-pressure homogenizer. A high-pressure homogenization reaction is carried out at a temperature of 40 °C, a pH of 10, and a pressure of 30 MPa. After the reaction, it is aged for 12 h, followed by filtration, washing, and drying to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0059] The cathode material precursor A, sodium bicarbonate, and blend B (a mixture of calcium oxide, titanium hydroxide, and magnesium oxide with an elemental molar ratio of Ca:Ti:Mg = 5:4:4) are placed in a blender in a molar ratio of Na:A:B = 1.05:0.87:0.13 and stirred and mixed at a speed of 300 rpm to obtain a blend. The blend is sintered in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h, followed by pulverization to obtain a single-crystalline morphology sodium-ion battery layered cathode material Na 1.05 A 0.87 B 0.13 O 2 。

[0060] Example 3

[0061] (a) A transition metal salt solution with a concentration of 2 mol / L is prepared by combining nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate in an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. This solution, along with a 4 mol / L precipitating agent sodium hydroxide solution and a 4 g / L complexing agent ammonia water, is added to a high-pressure homogenizer. A high-pressure homogenization reaction is carried out at a temperature of 40 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, it is aged for 14 h, followed by filtration, washing, and drying to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0062] The cathode material precursor A, sodium oxalate, and blend B (a mixture of calcium peroxide, titanium hydroxide, and magnesium carbonate with an elemental molar ratio of Ca:Ti:Mg = 4:3:6) are placed in a blender in a molar ratio of Na:A:B = 1.03:0.87:0.13 and stirred and mixed at a speed of 300 rpm to obtain a blend. The blend is sintered in an air atmosphere at 600 °C for 4 h and then at 1000 °C for 17 h, followed by pulverization to obtain a single-crystalline morphology sodium-ion battery layered cathode material Na1.03 A 0.87 B 0.13 O 2 。

[0063] Example 4

[0064] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate in an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04 to form a 2 mol / L transition metal salt solution. Add it to a high-pressure homogenizer together with a 4 mol / L precipitant sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 12, and a pressure of 40 MPa. After the reaction ends, age for 14 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0065] Put the cathode material precursor A, sodium citrate, and blend B (a mixture of calcium hydroxide, titanium hydroxide, and magnesium carbonate, with an elemental molar ratio of Ca:Ti:Mg = 5:2:6) into a blender in a molar ratio of Na:A:B = 1.00:0.87:0.13. Stir and mix at a rotation speed of 500 rpm to obtain a blend. Sinter the blend in an air atmosphere at 600 °C for 6 h and then at 900 °C for 15 h, and crush to obtain a single-crystalline morphology sodium-ion battery layered cathode material Na 1.00 A 0.87 B 0.13 O 2 。

[0066] Example 5

[0067] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate in an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04 to form a 2 mol / L transition metal salt solution. Add it to a high-pressure homogenizer together with a 5 mol / L precipitant sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 12, and a pressure of 20 MPa. After the reaction ends, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0068] Put the cathode material precursor A, sodium carbonate, and blend B (a mixture of calcium sulfate, titanium oxide, and magnesium nitrate with an elemental molar ratio of Ca:Ti:Mg = 4:3:6) into a blender at a molar ratio of Na:A:B = 1.00:0.87:0.13, and stir and mix at a rotation speed of 500 rpm to obtain a blend. Sinter the blend in an air atmosphere at 600 °C for 4 h and then at 900 °C for 20 h, and pulverize to obtain a layered cathode material for a sodium-ion battery with a single-crystal morphology, Na 1.00 A 0.87 B 0.13 O 2 。

[0069] Example 6

[0070] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate into a 2 mol / L transition metal salt solution at an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitant sodium hydroxide solution and a 4 g / L complexing agent ammonia water. Carry out a high-pressure homogenization reaction at a temperature of 60 °C, a pH of 10, and a pressure of 30 MPa. After the reaction, age for 11 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0071] Put the cathode material precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, titanium dichloride, and magnesium nitrate with an elemental molar ratio of Ca:Ti:Mg = 5:4:4) into a blender at a molar ratio of Na:A:B = 1.03:0.87:0.13, and stir and mix at a rotation speed of 500 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h, and pulverize to obtain a layered cathode material for a sodium-ion battery with a single-crystal morphology, Na 1.03 A 0.87 B 0.13 O 2 。

[0072] Example 7

[0073] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate to form a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitating agent sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 40 MPa. After the reaction, age for 13 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0074] Put the cathode material precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, titanium trichloride, and magnesium acetate, with an elemental molar ratio of Ca:Ti:Mg = 5:4:4) into a blender according to the molar ratio of Na:A:B = 1.03:0.80:0.20. Stir and mix at a speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h, and pulverize to obtain a sodium-ion battery layered cathode material with a single-crystal morphology, Na 1.03 A 0.80 B 0.20 O 2 。

[0075] Example 8

[0076] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate to form a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitating agent sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out a high-pressure homogenization reaction at a temperature of 60 °C, a pH of 11, and a pressure of 20 MPa. After the reaction, age for 10 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0077] Put the cathode material precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, titanium tetrachloride, and magnesium acetate, with an elemental molar ratio of Ca:Ti:Mg = 4:4:5) into a blender according to the molar ratio of Na:A:B = 1.03:0.80:0.20. Stir and mix at a speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1100 °C for 10 h, and pulverize to obtain a sodium-ion battery layered cathode material with a single-crystal morphology, Na1.03 A 0.80 B 0.20 O 2 。

[0078] Example 9

[0079] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate into a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitating agent sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0080] Put the cathode material precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, metatitanic acid, and magnesium oxide, with an elemental molar ratio of Ca:Ti:Mg = 5:3:5) into a blender according to the molar ratio of Na:A:B = 1.03:0.80:0.20. Stir and mix at a rotation speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1100 °C for 10 h, and pulverize to obtain the single-crystalline morphology sodium-ion battery layered cathode material Na 1.03 A 0.80 B 0.20 O 2 。

[0081] Example 10

[0082] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate into a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitating agent sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0083] (b) Mix the precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, titanium hydroxide, and magnesium oxide with an elemental molar ratio of Ca:Ti:Mg = 5:3:5) in a molar ratio of Na:A:B = 1.03:0.87:0.13 in a blender, stir and mix at a rotation speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h, and pulverize to obtain a layered cathode material for a sodium-ion battery with a single-crystal morphology, Na 1.03 A 0.87 B 0.13 O 2 。

[0084] Comparative Example 1

[0085] Taking Example 10 as a reference, in Comparative Example 1, by reducing the sintering temperature, the effects on the morphology and properties of the material were investigated. The preparation method is as follows:

[0086] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate in an elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04 to form a 2 mol / L transition metal salt solution, and add it to a high-pressure homogenizer together with a 4 mol / L precipitant sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Carry out a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0087] (b) Mix the precursor A, sodium carbonate, and blend B (a mixture of calcium carbonate, titanium hydroxide, and magnesium oxide with an elemental molar ratio of Ca:Ti:Mg = 5:3:5) in a molar ratio of Na:A:B = 1.03:0.87:0.13 in a blender, stir and mix at a rotation speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 850 °C for 15 h, and pulverize to obtain a layered cathode material for a sodium-ion battery with a polycrystalline morphology, Na 1.03 A 0.87 B 0.13 O 2 。

[0088] Comparative Example 2

[0089] Taking Example 10 as a reference, in Comparative Example 2, no elements were doped in step b, and the effects of doping elements on the morphology and properties of the material were investigated. The preparation method is as follows:

[0090] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate into a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitant sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Conduct a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0091] (b) Add the precursor A and sodium carbonate into a blender according to the elemental molar ratio of Na:Ni:Fe:Mn:Zr = 1.03:0.32:0.32:0.32:0.04. Stir and mix at a rotation speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h. Crush to obtain the single-crystalline morphology sodium-ion battery layered cathode material Na 1.03 Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 O 2 。

[0092] Comparative Example 3

[0093] Taking Example 10 as a reference, in Comparative Example 3, only Ca element is doped in step b to investigate the influence of a single doped element on the morphology and performance of the material. The preparation method is as follows:

[0094] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate into a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Add it to a high-pressure homogenizer together with a 4 mol / L precipitant sodium hydroxide solution and a 5 g / L complexing agent ammonia water. Conduct a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0095] (b) Put the precursor A, sodium carbonate, and calcium carbonate into a blender according to the elemental molar ratio of Na:Ni:Fe:Mn:Zr:Ca = 1.03:0.2784:0.2784:0.2784:0.0348:0.13, stir and mix at a speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h, and pulverize to obtain a single-crystalline morphology sodium-ion battery layered cathode material Na 1.03 Ni 0.2784 Fe 0.2784 Mn 0.2784 Zr 0.0348 Ca 0.13 O 2 。

[0096] Comparative Example 4

[0097] Taking Example 10 as a reference, in Comparative Example 4, only Ti element was doped in step b to investigate the influence of a single doping element on the morphology and performance of the material. The preparation method is as follows:

[0098] (a) Combine nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate into a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04, add 4 mol / L precipitant sodium hydroxide solution and 5 g / L complexing agent ammonia water to a high-pressure homogenizer, carry out a high-pressure homogenization reaction at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, age for 12 h, filter, wash, and dry to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0099] (b) Put the precursor A, sodium carbonate, and doping element Ti into a blender according to the elemental molar ratio of Na:Ni:Fe:Mn:Zr:Ti = 1.03:0.2784:0.2784:0.2784:0.0348:0.13, stir and mix at a speed of 400 rpm to obtain a blend. Sinter the blend in an air atmosphere at 500 °C for 5 h and then at 1000 °C for 15 h, and pulverize to obtain a single-crystalline morphology sodium-ion battery layered cathode material Na 1.03 Ni 0.2784 Fe 0.2784 Mn 0.2784 Zr 0.0348 Ti 0.13 O 2 。

[0100] Comparative Example 5

[0101] Taking Example 10 as a reference, in Comparative Example 5, only Mg element was doped in step b to investigate the influence of a single doped element on the morphology and properties of the material. The preparation method is as follows:

[0102] (a) Nickel sulfate, ferrous sulfate, manganese sulfate, and zirconium sulfate were combined into a 2 mol / L transition metal salt solution according to the elemental molar ratio of Ni:Fe:Mn:Zr = 0.32:0.32:0.32:0.04. Sodium hydroxide solution as a 4 mol / L precipitant and ammonia water as a 5 g / L complexing agent were added to a high-pressure homogenizer, and high-pressure homogenization reaction was carried out at a temperature of 50 °C, a pH of 11, and a pressure of 30 MPa. After the reaction, it was aged for 12 h, filtered, washed, and dried to obtain the cathode material precursor A, Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 。

[0103] (b) The precursor A, sodium carbonate, and the doped element Mg were put into a blender according to the elemental molar ratio of Na:Ni:Fe:Mn:Mg = 1.03:0.2784:0.2784:0.2784:0.0348:0.13, and stirred and mixed at a rotation speed of 400 rpm to obtain a blend. The blend was sintered at 500 °C for 5 h and sintered at 1000 °C for 15 h in an air atmosphere, and then pulverized to obtain a single-crystal morphology sodium-ion battery layered cathode material Na 1.03 Ni 0.2784 Fe 0.2784 Mn 0.2784 Zr 0.0348 Mg 0.13 O 2 。

[0104] Comparative Example 6

[0105] In this example, a high-temperature sintering process was directly carried out using oxides. The specific steps are as follows:

[0106] Sodium carbonate, nickel oxide, iron(III) oxide, manganese dioxide, zirconium oxide, calcium oxide, titanium dioxide, and magnesium oxide were put into a blender according to the elemental molar ratio of Na:Ni:Fe:Mn:Zr:Ca:Ti:Mg = 1.03:0.2784:0.2784:0.2784:0.0348:0.05:0.03:0.05, and stirred and mixed at 400 rpm to obtain a blend. The blend was sintered at 500 °C for 5 h and sintered at 1000 °C for 15 h in an air atmosphere, and then pulverized to obtain a single-crystal morphology sodium-ion battery layered cathode material Na 1.03 Ni 0.2784 Fe 0.2784 Mn 0.2784 Zr 0.0348 Ca0.05 Ti 0.03 Mg 0.05 O 2 。

[0107] Structure confirmation:

[0108] As Figures 1 to 3 shown, the SEM and XRD diagrams of the precursors and layered cathode materials prepared in Comparative Example 1 and Example 10 of the present invention are presented.

[0109] As Figure 1 shown, during the preparation of the precursor, by adjusting the concentration of the complexing agent ammonia water, pH, temperature, aging time, etc., it is possible to promote the precursor of the cathode material Ni 0.32 Fe 0.32 Mn 0.32 Zr 0.04 (OH) 2 to have a D v 50 between 3 - 5 μm, BET between 20 - 22 m 2 / g, and the tapped density between 1.2 - 1.4 g / cm 3 . The morphology is secondary spherical particles composed of non - directionally densely packed flaky structures, and its SEM diagram is as Figure 1 shown. Among them, the concentration of ammonia water has a great influence on the morphology of the product. When the concentration is low, the morphology of the precursor is relatively loose, and an increase in concentration will lead to an increase in the tapped density. In addition, the pH value has an important influence on the growth process of the precursor. By adjusting the pH, the morphology of the primary grains and secondary particles can be controlled. When the pH value is low, it is conducive to the growth of crystal nuclei, and the primary grains are thicker and larger; when the pH value is high, it is conducive to the formation of crystal nuclei, and the primary grains are in the form of thin flakes and appear very small. The influence on the secondary particles is as follows: when the pH value is low, the secondary particles are prone to agglomeration, resulting in abnormal - shaped secondary spheres; when the pH is high, the secondary particles are mostly spherical.

[0110] Combined with Figure 3 shown: Figure 3 In, the left - hand view is the layered cathode material prepared in Comparative Example 1, with a polycrystalline morphology, which is secondary spherical particles formed by the agglomeration of primary particles, and there are a large number of grain boundaries inside. Figure 3 The right - hand view of

[0111] is the layered cathode material prepared in Example 10, with a single - crystal morphology. This is because the high - temperature calcination temperature in Example 10 is higher than that in Comparative Example 1. Increasing the calcination temperature promotes ion migration, increases the grain growth rate, and gradually forms a single crystal.

[0112] Performance test:

[0113] (1) Electrochemical performance

[0114] The sodium-ion battery layered cathode material powders prepared in the foregoing examples and comparative examples were ground and passed through a 200-mesh sieve, and then formulated with SP (conductive carbon black) and PVDF (polyvinylidene fluoride) at a mass ratio of 8:1:1. NMP (N-methylpyrrolidone) was added and stirred into a slurry, which was coated on aluminum foil. After drying, punching, and pressing, a sodium-ion battery cathode material electrode sheet was made. Using metallic sodium as the anode, glass fiber (grade Whatman GF / D) as the separator, and the electrolyte being a NaPF6 (sodium hexafluorophosphate) PC (propylene carbonate) / EMC (ethyl methyl carbonate) solution, a CR2025 button battery was assembled in a glove box filled with argon for charge and discharge tests. At a current density of 100 mAh / g and a voltage range of 2.0 - 4.0 V / 4.1 V, it was first cycled at 0.2 C for 2 cycles, and then the capacity and cycle performance were tested at 1 C.

[0115] (2) Particle size

[0116] The measurement was carried out according to the national standard GB / T19077 - 2016 particle size distribution wide-angle X-ray diffraction method.

[0117] (3) BET

[0118] The measurement of the specific surface area of solid substances was carried out according to the national standard GB / T 19587 - 2017 gas adsorption BET method.

[0119] The test results are shown in Table 1 and Table 2:

[0120] Table 1. Electrochemical performance table of Comparative Examples 1 - 6 and Examples 1 - 10

[0121]

[0123] Table 2. Physical and chemical properties table of Comparative Examples 1 - 6 and Examples 1 - 10

[0124] Serial number <![CDATA[Particle size D v 50 / μm]]> <![CDATA[I (003) / I (104) > <![CDATA[BET / m 2 ·g -1 > Comparative example 1 9.7 0.729 0.696 Comparative example 2 4.3 0.699 0.650 Comparative example 3 5.1 0.685 0.652 Comparative example 4 4.8 0.693 0.600 Comparative example 5 5.1 0.696 0.628 Comparative example 6 8.4 0.698 0.639 Example 1 7.0 0.658 0.469 Example 2 7.2 0.645 0.459 Example 3 6.9 0.652 0.475 Example 4 7.4 0.648 0.440 Example 5 7.7 0.637 0.436 Example 6 6.3 0.646 0.486 Example 7 7.2 0.641 0.469 Example 8 6.9 0.639 0.472 Example 9 7.8 0.645 0.457 Example 10 7.3 0.634 0.496 。

[0125] Analysis: Combining Table 1 - Table 2, Figures 4 to 6 as shown

[0126] (1) As can be seen from Table 1, compared with Comparative Examples 1 - 5, the cathode materials prepared in Examples 1 - 10 have more excellent electrochemical performance and cycle performance. Taking Comparative Example 1 and Example 10 as an example, Comparative Example 1 is a polycrystalline material while Example 10 is a single crystal material. The capacity retention rate of Example 10 after 200 cycles of button cell charge and discharge is higher than that of Comparative Example 1 (Table 1, Figure 6), because there is no grain boundary inside the single crystal material, it can effectively deal with grain boundary crushing and electrolyte penetration, thereby obtaining better cycle performance. Comparative Example 2 and Example 10 have the same preparation process, but no element modification is doped in Comparative Example 2. Compared with Example 10, the discharge specific capacity and cycle performance of Comparative Example 2 are poor. This is because the element Ca doped in Example 10 has a larger radius, which can expand the unit cell parameters of the positive electrode material, is conducive to the diffusion of sodium ions, and has a better discharge specific capacity. Doping into Ti and Mg elements can further improve the cycle performance of the material. Comparative Examples 3-5 have the same preparation process as Comparative Example 2, but the difference is that Comparative Examples 3-5 are doped with different single elements. It can be seen from Table 1 that the discharge specific capacity (2-4.0V 0.2C) of Comparative Example 3 is 3mAh / g higher than that of Comparative Example 2, indicating that the addition of Ca is conducive to the increase of the discharge specific capacity of the material. The addition of Ti and Mg elements makes the cycle performance of Comparative Examples 4 and 5 higher than that of Comparative Example 2. Comparative Example 6 uses oxide raw materials for sintering, but the single crystal positive electrode material prepared therefrom has a 2-4V 0.2C discharge specific capacity of only 115.31 mAh / g, and the cycle performance is not improved. This is because the sample uniformity is poor, and it is impossible to use the co-precipitation method to obtain a precursor as in Example 10, in which the elements are evenly mixed and further sintered to obtain a positive electrode material with better performance.

[0127] (2) By adjusting the precursor preparation process parameters, the positive electrode material sintering process parameters and the element ratio, during the sintering process of the positive electrode material, the increase in temperature causes the material particle size to increase (Examples 9 and 10), which further causes the discharge specific capacity of the material to decrease. Compared with Example 10, the sodium content in Example 2 increases, which increases the discharge specific capacity of the material, but the cycle retention rate of Example 2 is lower than that of Example 10. Combining Tables 1 and 2, Example 10 has the best comprehensive performance, and the crystal form of the material in Example 10 is still O3 type ( Figure 2 The electrochemical performance of its positive electrode material is 137.88mAh / g at 2-4.0V and 0.2C. Figure 5 ), the capacity retention rate after 200 cycles at 1C is 87.9% ( Figure 6 ). The discharge capacity reaches 144.23 mAh / g at 2-4.1 V and 0.2 C, and the capacity retention rate after 200 cycles at 1 C is 85.3%.

[0128] Those skilled in the art will easily understand that the above descriptions are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-capacity sodium-ion battery layered positive electrode material, characterized in that: The layered positive electrode material is a single crystal O3 type, and its chemical formula is: Na 1+a M 1 (1-b) M 2 b O2, where 0.00≤a≤0.05, 0.1≤b≤0.3; M 1 M is a transition metal element. 2 is a doping element, the M 1 One or more of Ni, Fe, Mn, Co, Zr and Cu; the M 2 One or more selected from Ca, Cu, Sr, Al, Ti, Zn, Zr, Mg and Co.

2. A high-capacity sodium ion battery layered positive electrode material according to claim 1, characterized in that: In the layered positive electrode material, 0.01≤a≤0.

03.

3. The high-capacity sodium ion battery layered positive electrode material according to claim 1, characterized in that: In the layered positive electrode material, the transition metal element M 1 It is a mixture of Ni, Fe, Mn and Zr, 0.8≤1-b≤0.9, wherein the element molar ratio of Ni, Fe, Mn and Zr is 0.30-0.32:0.30-0.32:0.30-0.32:0.01-0.

10.

4. The high-capacity sodium ion battery layered positive electrode material according to claim 1, characterized in that: In the layered positive electrode material, the doping element M 2 It is a mixture of Ca, Ti and Mg, 0.1≤b≤0.2, wherein the element molar ratio of Ca, Ti and Mg is 4-6:2-4:4-6.

5. The high-capacity sodium ion battery layered positive electrode material according to claim 1, characterized in that: The layered positive electrode material is a single crystal O3 type, and the shape of the single crystal particles is one of spherical, quasi-spherical, polyhedral, and lamellar, or a mixture of two or more thereof.

6. The high-capacity sodium ion battery layered positive electrode material according to claim 1, characterized in that: The layered positive electrode material, the transition metal element M 1 It is a mixture of Ni, Fe, Mn and Zr, wherein the molar ratio of Ni, Fe, Mn and Zr is 0.32:0.32:0.32:0.04; the doping element M 2 It is a mixture of Ca, Ti and Mg, wherein the element molar ratio of Ca, Ti and Mg is 5:3:5, and b=0.

13.

7. A method for preparing a high-capacity sodium ion battery layered positive electrode material, comprising the following steps: (a) The 1 Sulfates of the elements are combined into a transition metal salt solution of a certain concentration, which is added into a high-pressure homogenizer together with a precipitant and a complexing agent, and a high-pressure homogenization reaction is carried out at a certain temperature, pH and pressure. After the reaction is completed, the solution is aged, filtered, washed and dried to obtain a cathode material precursor. (b) The cathode material precursor, sodium source, and doping element M 2 The mixture is put into a mixer in a certain proportion, stirred and mixed at a certain speed to obtain a blend, sintered in a certain atmosphere and at a certain temperature, and crushed to obtain a high-capacity single-crystal O3 sodium-ion battery layered positive electrode material.

8. The method for preparing a high-capacity sodium ion battery layered positive electrode material according to claim 7, characterized in that: The homogeneous reaction in step (a) has a reaction temperature of 40-60° C., a pH of 10-12, and a pressure of 20-40 MPa.

9. The method for preparing a high-capacity sodium ion battery layered positive electrode material according to claim 7, characterized in that: The sintering in step (b) is carried out in an air atmosphere, first at 400-600° C. for 3-6 h, and then at 900-1200° C. for 10-20 h.

10. Use of the high-capacity sodium ion battery layered positive electrode material according to claim 1 in preparing a sodium ion battery.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN117239081A

  • Sodium battery positive electrode material, positive electrode plate and preparation method and application thereof

    CN118198316A

Cited By

  • Sodium ion positive electrode material and preparation method thereof

    CN120978061A

  • Method for synthesizing precursor of layered oxide positive electrode material of sodium-ion battery by solid precipitation method

    CN121717408A

  • Synthesis method of large single crystal sodium ion battery layered oxide positive electrode material

    CN122257093A